2017
DOI: 10.1136/annrheumdis-2017-211751
|View full text |Cite
|
Sign up to set email alerts
|

Abatacept in the treatment of adult dermatomyositis and polymyositis: a randomised, phase IIb treatment delayed-start trial

Abstract: In this pilot study, treatment of patients with DM and PM with abatacept resulted in lower disease activity in nearly half of the patients. In patients with repeat muscle biopsies, an increased frequency of Foxp3 Tregs suggests a positive effect of treatment in muscle tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 24 publications
2
70
2
6
Order By: Relevance
“…Tjärnlund et al (2018) was a randomized trial using intravenous abatacept either as an immediate start or a 3-month delayed start for patients with refractory dermatomyositis or polymyositis. 4 After 6 months of treatment, 47% of patients overall had met the study's definition of improvement. It was noted however, that four mild and four moderate adverse events were caused by the drug.…”
Section: Related Literaturementioning
confidence: 99%
“…Tjärnlund et al (2018) was a randomized trial using intravenous abatacept either as an immediate start or a 3-month delayed start for patients with refractory dermatomyositis or polymyositis. 4 After 6 months of treatment, 47% of patients overall had met the study's definition of improvement. It was noted however, that four mild and four moderate adverse events were caused by the drug.…”
Section: Related Literaturementioning
confidence: 99%
“…A phase IIb clinical trial evaluating the efficacy of abatacept in patients with refractory SAM demonstrated few serious adverse effects in approximately half of the patients' responses based on the criteria established by the International Myositis Assessment and Clinical Studies Group (IMACS) (B) [75].…”
Section: How Long Should Sam Patients Receive Immunosuppressive / Immmentioning
confidence: 99%
“…Se han usado en DM, PM y MCI como tercera línea. Estos actúan en múltiples niveles de la respuesta inflamatoria (Tabla 6) [66][67][68][69][70][71][72][73] conocerlos ya que han abierto una nueva ventana de manejo.…”
Section: Tratamientos Biológicosunclassified